GAMBARAN FAAL PARU PEKERJA NON KESEHATAN LAKI-LAKI DI RSUD BANGKINANG - Ikhsan Fajri; Eka Bebasari; Indra Yovi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTSmoking is the main cause of death in the world, but it’s preventable. From the WHO data, in the 20th, 100 million people around the world has died due to smoking. Indonesia also has a probability of the increasement of smokers, especially to teenagers. The purpose of this researh was to discover/notice the pulmonary function overview of smoker and non-smoker groups based on the spirometry result. The number of subyects in this research were 107 non medical male workers of the Bangkinang General Hospital which consist of 33 smokers and 74 non smokers. This researh was a descriptive study with a cross-sectional approach. The sampling technique used by total sampling. The result of this researh showed that the highest number of respondents from the age of 26-35 years old (49,53%), the group of non smokers with the number of 74 people (69,15%), the people with a normal cathegory of nutritional status with the number of 87 people (81,30%), and all showed they don’t have the history of obstruction damages. The overview of smoking degrees on the group of smokers based on the Brinkman index was light-smoker (72,72%). In this reseach, a number of 42,42% of respondents from the smoker-group had an obstructive function, and 67,56% of respondents from the group of non smokers had a normal pulmonary function.Keywords : Smoker, pulmonary function, spirometry, non medical workers